2017
DOI: 10.1016/j.redox.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aldehyde dehydrogenase-2 deficiency compromises therapeutic effect of ALDH bright cell on peripheral ischemia

Abstract: The autologous ALDH bright (ALDHbr) cell therapy for ischemic injury is clinically safe and effective, while the underlying mechanism remains elusive. Here, we demonstrated that the glycolysis dominant metabolism of ALDHbr cells is permissive to restore blood flow in an ischemic hind limb model compared with bone marrow mononuclear cells (BMNCs). PCR array analysis showed overtly elevated Aldh2 expression of ALDHbr cells following hypoxic challenge. Notably, ALDHbr cells therapy induced blood flow recovery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…ALDH2 activity regulates mitochondrial homeostasis and function by combating oxidative stress [ 20 , 33 ]. Therefore, we treated mitochondria with ALDH2 activator, Alda-1, to determine the effect on mitochondrial respiration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ALDH2 activity regulates mitochondrial homeostasis and function by combating oxidative stress [ 20 , 33 ]. Therefore, we treated mitochondria with ALDH2 activator, Alda-1, to determine the effect on mitochondrial respiration.…”
Section: Resultsmentioning
confidence: 99%
“…As a mitochondrial enzyme, ALDH2 plays a pivotal role in sustaining the mitochondrial homeostasis of cardiomyocytes [ 19 , 20 , 45 ]. Our previous studies elucidated that ALDH2 deficiency [ 20 , 33 ] or inhibition [ 46 ] stimulated ROS over-production in mitochondria, ultimately resulting in exacerbated cardiomyocyte apoptosis in response to hypoxia. Thus, the close relationship between ALDH2 activity and mitochondrial homeostasis prompted the present study on ALDH2 activation in mitochondrial transplantation.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that low expression of ALDH in decidual MSC (DMSC) isolated from preeclamptic (PE) patients is associated with reduced resistance to cell toxicity. In line, stem and progenitor cells expressing high level of ALDH were shown to be clinically safe and effective cell therapy for peripheral ischemia [ 42 ]. These cyto-protective enzymes may thus potentiate cell therapy by serving as markers of highly therapeutic MSCs that harbor specific competencies.…”
Section: Discussionmentioning
confidence: 99%
“…High level of oxidative phosphorylation in mitochondria has been known to produce oxidative stress such as ROS. On the other hand, previous studies provided evidences that ALDH family proteins help alleviate intracellular ROS (36)(37)(38). The underlying mechanism is attributable to their capability in clearage of cellular aldehydes, which are known as ROS inducer (39)(40)(41).…”
Section: Aldh1a2 Reduces the Level Of Reactive Oxygen Species (Ros) Imentioning
confidence: 99%